Apologi Teologis atas Ibn'Arabi : Analisis Kritis Kitab Al-Yawaqit wa al-Jawahir fi 'Aqaid al-Akabir Karya Imam Sya'rani - Ikhbar F Zifamina (UIN Sunan Kalijaga Yogyakarta, 2021)
Ibn ‘Arabi is a great sufi master in the history of Islam that is often misunderstood and revered and yet defended in theological matters. One of the Islamic scholars who defended Ibn ‘Arabi in theological context was Imam Abdul Wahhab Asy-Sya’rani. His book, entitled al-Yawaqit wa al-Jawahir fi Bayan ‘Aqaid al-Akabir, contained a script beetwen kalam and tasawuf especially an apology of Imam Sya’rani that to defense Ibn ‘Arabi according to the Futuhat al-Makkiyyah. This reseacrh focuses on the study of the book by critical analysis of the apology or defense of Imam Sya’rani over Ibn ‘Arabi in theological context, esepecially on the problem of tanzih (trancendece) and tasybih(immanence). The urgency of this study to show the dialectic of both Islamic discourses, kalam and tasawuf, which intertwined with each other and open a dialogue space beetwen of two. Hence, this study uses a theological approach with critical analysis method. The author of the study then found that : First, Al-Yawaqit wa al-Jawahir indicates that Imam Sya’rani in tanzih and tasybih more like a Ibn ‘Arabi’s synthesis or harmonization either. Second, the theological apology of Imam Sya’rani which defense Ibn ‘Arabi is more apologetic and justifical with jawab wa su’al response pattern as the mutakallim.